Examining the Role of Stressful Events and the Behavioral Brain System in Youth Addiction Tendencies in Yasuj - Mosaei Sisakht, Fatemeh; Maredpour, Alireza; Ramezani, Khosro (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Drug use, considered a socially unacceptable habit across all human societies, has involved countless individuals, particularly from adolescence and youth to middle age. This study aimed to determine the role of stressful events and the behavioral brain system in addiction tendencies among the youth of Yasuj.Methods and Materials: This study was descriptive and correlational in nature. The statistical population included all young people aged 18 to 35 years in Yasuj in 2022. Based on the Krejcie and Morgan table (1987) and using multi-stage cluster random sampling, 384 young people from Yasuj were selected and studied. Data collection was conducted using the Holmes and Rahe Stressful Life Events Questionnaire (1960), the Behavioral Inhibition/Activation System by Carver and White (1994), and the Addiction Potential Scale by Weed and Butcher (1992). After data collection and extraction, the participants' scores were analyzed using Pearson's correlation coefficient and the fitted values, with the help of SPSS-24 statistical software.Findings: The results of Pearson's correlation coefficient showed a significant positive relationship between stressful life events and addiction tendencies among the youth of Yasuj (P < 0.01). There was a significant negative relationship between the behavioral inhibition system and addiction tendencies among the youth of Yasuj (P < 0.01). There was a significant positive relationship between the behavioral activation system and addiction tendencies among the youth of Yasuj (P < 0.01).Conclusion: Based on the results, by identifying stressful life events and the behavioral activation system in young people, measures can be taken to prevent their tendency toward addiction.